Phytochemicals and Amino Acids Profiles of Selected sub-Saharan African Medicinal Plants' Parts Used for Cardiovascular Diseases' Treatment - Johnson Oluwaseun Odukoya; Julianah Olayemi Odukoya; Edwin Mpoh Mmutlane; Derek Tantoh Ndinteh (MDPI AG, 2021)
For years, the focus on the lipid-atherosclerosis relationship has limited the consideration of the possible contribution of other key dietary components, such as amino acids (AAs), to cardiovascular disease (CVD) development. Notwithstanding, the potential of plant-based diets, some AAs and phytochemicals to reduce CVDs' risk has been reported. Therefore, in this study, the phytochemical and AA profiles of different medicinal plants' (MPs) parts used for CVDs' treatment in sub-Saharan Africa were investigated. Fourier-transform infrared analysis confirmed the presence of hydroxyl, amino and other bioactive compounds' functional groups in the samples. In most of them, glutamic and aspartic acids were the most abundant AAs, while lysine was the most limiting. P. biglobosa leaf, had the richest total branched-chain AAs (BCAAs) level, followed by A. cepa bulb. However, A. cepa bulb had the highest total AAs content and an encouraging nutraceutical use for adults based on its amino acid score. Principal component analysis revealed no sharp distinction between the AAs composition of MPs that have found food applications and those only used medicinally. Overall, the presence of medicinally important phytochemicals and AAs levels in the selected MPs' parts support their use for CVDs treatment as they might not add to the AAs (e.g., the BCAAs) burden in the human body.